2022
DOI: 10.1155/2022/6093613
|View full text |Cite
|
Sign up to set email alerts
|

Speech as a Biomarker for COVID-19 Detection Using Machine Learning

Abstract: The use of speech as a biomedical signal for diagnosing COVID-19 is investigated using statistical analysis of speech spectral features and classification algorithms based on machine learning. It is established that spectral features of speech, obtained by computing the short-time Fourier Transform (STFT), get altered in a statistical sense as a result of physiological changes. These spectral features are then used as input features to machine learning-based classification algorithms to classify them as coming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Machine learning is applied extensively in biomedical applications, as well as COVID-19 diagnosis ( 8 ). Extreme Gradient Boosting (XGBoost) is a GBDT-based algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is applied extensively in biomedical applications, as well as COVID-19 diagnosis ( 8 ). Extreme Gradient Boosting (XGBoost) is a GBDT-based algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…During the ongoing coronavirus disease 2019 (COVID-19) pandemic, researchers have shown the effectiveness of ML in various fields ( 32 34 ); however, potential applications of ML for disease prevention are unclear in real-world medical settings. Furthermore, translational bioinformatics in COVID-19 research has suggested the effectiveness of ML models with customized designs ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…6 Omicron, however, more commonly affects the upper airway, sinuses, and hypopharynx than prior variants, often resulting in voice changes without a cough. 7 This represents an opportunity for more specific targeting by AI methods if robust datasets were available. Worldwide, there are over 3.6 billion users of various social media platforms, and that number is expected to be above 4.4 billion by 2025.…”
Section: Introductionmentioning
confidence: 99%
“…Prior AI methods have been unable to successfully detect pre-Omicron variants from unscripted or scripted human voice alone, or have been otherwise unsuitable for deployment (e.g., limited training data, poor generalization) 5 . Omicron variants, however, are typically milder and affect the upper airway more commonly than prior variants, often resulting in voice changes without a cough or other respiratory symptoms 6 . This presents an opportunity for targeting with AI methods, if robust datasets were available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation